Psycholinguistic problems and risks of online language and speech testing - T. S. Putilovskaya; I. G. Tuchkova; E. V. Zubareva (Вестник университета)
The article deals with the psycholinguistic problems and risks related to preparing, organising and conducting online foreign language testing which is firmly entrenched in the education system as a convenient and objective form of control. The authors study the linguistic and didactic aspects of computer-based testing, psychological issues related to students’ activities and analyse the results of the survey aimed at revealing the emerging difficulties and risks. The paper aim is to maximise the quality of test tasks, minimise possible psychological difficulties and improve the effectiveness of preparing students for the testing period by means of developing the necessary language and speech skills, as well as psychological readiness. The survey data shows that most students have positive opinion concerning online testing and give adequate assessment of its difficulty level. They demonstrate readiness to adapt their activities to the requirements of such test format.